„Valami bűzlik Dániában”: Janne Teller Semmi című ifjúsági regénye - Kovács, Gergely (Studia Litteraria, 2019)
Even though Denmark is considered to be one of the happiest countries, one of the unhappiest teenage stories originates from there. In Janne Teller’s first scandalous then successful youth novel a fourteen-year-old boy claims that it is not worth doing anything as nothing matters, so his classmates started a collecting game to prove him the opposite, ending up in tragic sacrifices. This essay examines the novel from the perspective of meaningful activities, based on Mihály Csíkszentmihályi’s studies titled The Meaning of Things, Being Adolescent, and Flow: The Psychology of Optimal Experience. The study also compares the novel to the well-known youth story The Boys of Paul Street by Ferenc Molnár, as both works depict the teenagers’ struggles to adapt to the adults’ controversial expectations.